2016
DOI: 10.1186/s12978-016-0229-6
|View full text |Cite
|
Sign up to set email alerts
|

Adequacy of public maternal care services in Brazil

Abstract: BackgroundIn Brazil, hospital childbirth care is available to all, but differences in access and quality of care result in inequalities of maternal health. The objective of this study is to assess the infrastructure and staffing of publicly financed labor and birth care in Brazil and its adequacy according to clinical and obstetric conditions potentially associated with obstetric emergencies.MethodsNationwide cross-sectional hospital-based study “Birth in Brazil: national survey into labor and birth” conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
1
18

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(54 citation statements)
references
References 34 publications
0
32
1
18
Order By: Relevance
“…14 Furthermore, the literature shows that reference facilities should be no farther than 20 km away and that smaller maternities with few patients should be avoided when composing the healthcare system, as they present worse perinatal outcomes. 15 A population study on births in Brazil 14 showed that 10% to 24% of low-risk maternities were considered inadequate in terms of physical structure, support services, and human resources to provide quality care. Another example of this inadequacy was presented in a study that observed that obstetricians did not know how to use magnesium sulfate, a drug that is essential to the treatment of hypertensive emergencies in pregnancy, the leading cause of maternal death in Brazil.…”
mentioning
confidence: 99%
“…14 Furthermore, the literature shows that reference facilities should be no farther than 20 km away and that smaller maternities with few patients should be avoided when composing the healthcare system, as they present worse perinatal outcomes. 15 A population study on births in Brazil 14 showed that 10% to 24% of low-risk maternities were considered inadequate in terms of physical structure, support services, and human resources to provide quality care. Another example of this inadequacy was presented in a study that observed that obstetricians did not know how to use magnesium sulfate, a drug that is essential to the treatment of hypertensive emergencies in pregnancy, the leading cause of maternal death in Brazil.…”
mentioning
confidence: 99%
“…Dados semelhantes foram encontrados em pesquisa recente de abrangência nacional (14) , na qual faltavam equipamentos básicos para o atendimento de emergências obstétricas em 40% dos hospitais públicos sem UTI.…”
Section: Discussionunclassified
“…15 A pesquisa "Nascer no Brasil" avaliou os estabelecimentos de saúde públicos ou mistos, quanto à sua adequação às requisições das normativas nacionais, e encontrou que apenas 34,5% desses estabelecimentos encontravam-se adequados. 20 Nesse sentido, esse estudo reforça a falta de adequações desses serviços, como reforçado pela fala das mulheres identificadas nesta pesquisa.…”
Section: Subcategoria A3: Foco Na Infr Aestrutur a E Equipamentosunclassified